Effectiveness of syndecan-1 as an adjunct diagnostic marker in small bowel injury: a report of two cases - Hideshi Okada; Keiko Suzuki; Fuminori Yamaji; Tetsuya Fukuta; Masahiro Ichihashi; Yosuke Mizuno; Takahito Miyake; Norihide Kanda (Trauma Surgery & Acute Care Open)
Background Small bowel injuries are rare in trauma. Diagnosing these injuries is difficult owing to the lack of clear signs, and delays in diagnosis might increase complications and mortality. Trauma can damage the vascular endothelial glycocalyx, with syndecan-1 emerging as a marker of injury. Here, we describe two cases of small bowel injury due to traffic motor vehicle crash trauma.Case presentation The patients, one in their 40s and one teenaged, were transported to our hospital after a traffic motor vehicle crash. Both patients were wearing seat belts at the time of the motor vehicle crash, and the car’s airbags deployed properly. Their vital signs were stable at admission, and non-operative treatment was selected. However, their abdominal pain did not improve, and based on posthospitalization CT reconstructive imaging, intra-abdominal hemorrhage was suspected. Surgery was performed, revealing small intestinal injuries. In both patients, a high serum syndecan-1 level in the blood test at admission was a common characteristic.Conclusion Increased serum syndecan-1 level was observed in blood tests during the initial treatment of small intestinal injuries in these patients, suggesting its potential utility in early diagnosis. However, further accumulation of cases and detailed studies are required to substantiate these results.